KARAKTERISTIK SITIRAN PADA JURNAL PERPUSTAKAAN PERTANIAN BOGOR - Mafar, Fiqru (Jurnal Ilmu Budaya, 2010)
This study was carried out to find out citation literature characteristic, wich were published in the "Jurnal Perpustakaan Pertanian" during 2005-2009. The method focused on analyzing citation with the data references of article. The results of 10 issues consisting 44 articles and 311 cited literatures showed that most of the material references were books. The time publishing of literature that the most cited were 2001-2010, and age of literature that the most cited were 0-10 years old.